Autism spectrum traits predict the neural response to eye gaze in typical individuals - Nummenmaa L; Engell AD; von dem Hagen E; Henson RNA; Calder AJ (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Autism Spectrum Disorders (ASD) are neurodevelopmental disorders characterised by impaired social interaction and communication, restricted interests and repetitive behaviours. The severity of these characteristics are posited to lie on a continuum extending into the typical population, and typical adults' performance on behavioural tasks that are impaired in ASD is correlated with the extent to which they display autistic traits (as measured by Autism Spectrum Quotient, AQ). Individuals with ASD also show structural and functional differences in brain regions involved in social perception. Here we show that variation in AQ in typically developing individuals is associated with altered brain activity in the neural circuit for social attention perception while viewing others' eye gaze. In an fMRI experiment, participants viewed faces looking at variable or constant directions. In control conditions, only the eye region was presented or the heads were shown with eyes closed but oriented at variable or constant directions. The response to faces with variable vs. constant eye gaze direction was associated with AQ scores in a number of regions (posterior superior temporal sulcus, intraparietal sulcus, temporoparietal junction, amygdala, and MT/VS) of the brain network for social attention perception. No such effect was observed for heads with eyes closed or when only the eyes were presented. The results demonstrate a relationship between neurophysiology and autism spectrum traits in the typical (non-ASD) population and suggest that changes in the functioning of the neural circuit for social attention perception is associated with an extended autism spectrum in the typical population. (C) 2011 Elsevier Inc. All rights reserved.